2018
DOI: 10.3389/fnins.2018.00151
|View full text |Cite
|
Sign up to set email alerts
|

Changes in H-Reflex Recruitment After Trans-Spinal Direct Current Stimulation With Multiple Electrode Configurations

Abstract: Trans-spinal direct current stimulation (tsDCS) is an electro-modulatory tool with possible application in the rehabilitation of spinal cord injury. TsDCS generates a small electric field, aiming to induce lasting, functional neuromodulation in the targeted neuronal networks. Earlier studies have shown significant modulatory effects after application of lumbar tsDCS. However, for clinical application, a better understanding of application specific factors is required. Our goal was to investigate the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In the tsDCS trial there were also no changes in the H-reflex/M max ratio, consistent with previous studies in which anodal tsDCS applied for 15 min at the 11th thoracic vertebrae did not alter the soleus maximal H-reflex amplitude/M max ratio 20 , 52 . In contrast, Winkler, et al 20 reported that anodal tsDCS induced a lasting decrease in H-reflex post-activation depression, which may alter excitatory post-synaptic potentials.…”
Section: Discussionsupporting
confidence: 90%
“…In the tsDCS trial there were also no changes in the H-reflex/M max ratio, consistent with previous studies in which anodal tsDCS applied for 15 min at the 11th thoracic vertebrae did not alter the soleus maximal H-reflex amplitude/M max ratio 20 , 52 . In contrast, Winkler, et al 20 reported that anodal tsDCS induced a lasting decrease in H-reflex post-activation depression, which may alter excitatory post-synaptic potentials.…”
Section: Discussionsupporting
confidence: 90%
“…142) and were only rarely compatible with an increase in the excitability of group Ia afferents. The positive results of Lamy et al (143) and some other studies might nevertheless be most relevant (36,144,145) and (37) in humans and (33) in mice. Lamy et al (143) demonstrated that anodal tsDCS (2.5 mA applied for 15 min at Th11) was followed by ".…”
Section: Could Tsdcs Replicate the Effects Of Epiduralmentioning
confidence: 80%
“…Frequency and intensity of stimulation is known to affect the recruitment patterns of neuronal cells (Courtine et al, 2016). Stimulus received by spinal cord elements are intricately related to cell sizes, orientations, and positions with respect to the electrodes, anatomy, cellular and synaptic electrophysiology and morphology of spinal cord (Kuck et al, 2017, 2018).…”
Section: Discussionmentioning
confidence: 99%